Evaluasi Sistem Penyimpanan Limbah Bahan Berbahaya Dan Beracun Di PT. Guna Era Manufaktura Cikarang - Yusuf Dharmawan; Adhitya Ramadhan; Putri Anggun Sari (DPPM Universitas Pelita Bangsa, 2022)
B3 Waste (Toxic Hazardous Materials) is waste that harmful to the environment. B3 Waste (Toxic Hazardous Materials) is widely produced in industrial areas, especially by factories. Therefore, the processing of B3 waste (Toxic Hazardous Materials) is very important so that it must be regulated and monitored so that B3 waste (Toxic Hazardous Materials) does not pollute the environment. PT Guna Era Manufaktura is a company engaged in electricity and telecommunications located in the South Cikarang, Bekasi. Evaluation of the storage system at PT. Guna Era Manufacturing uses government regulation number 101 of 2014 concerning the management of hazardous and toxic waste as a quality standard in evaluating temporary storage areas. The evaluation method is descriptive evaluative where the results of the observations state that the temporary storage area of ​​PT. Guna Era Manufacturing has met the quality standard criteria. Keywords: Waste, Factory, Enviroment, Evaluation